A Study on Enhanced Cloud-Based Storage with Confidentiality Assurance, Verifiable Access Control, and Improved MD5 Schema - Devender Kumar , Sandeep Kumar Budhani , Saneh Lata Yadav , Prashant Vats , Shalendra Kumar , Govind Murari Upadhyay (International Journal of Intelligent Systems and Applications in Engineering, 2024)
Cloud-based storage solutions have revolutionized the way data is handled, saved, and accessed in today’s digital world. The guarantee of data confidentiality, the implementation of strong access control measures, and the verification of data integrity are the three main difficulties that have been highlighted by this paradigm shift. An in-depth analysis of these issues is provided in this paper, along with a thorough plan for improving cloud-based storage systems that include enhanced integrity validation, verifiable access control, and confidentiality guarantee via the use of an upgraded MD5 schema. Understanding the complexity of data security in cloud systems is fundamental to the suggested approach. Despite their ease and adaptability, conventional cloud storage strategies frequently fall. Conventional cloud storage solutions are convenient and scalable, but they frequently don’t sufficiently address the inherent risks that result from sharing infrastructure across several tenants. In response, our research promotes a comprehensive strategy that strengthens the security posture of cloud-based storage by combining cryptographic hashing, access control methods, and encryption approaches. The use of cutting-edge encryption methods to protect the privacy of stored data is a key component of our strategy. Before being sent to the cloud, data is encrypted using methods like AES (Advanced Encryption Standard), making it unintelligible to unauthorized parties. Users may feel confident about the privacy of their data since this guarantees that, even in the case of a breach or unauthorized access, critical information is shielded from prying eyes. Users may feel confident about the privacy of their data since this guarantees that, even in the case of a breach or unauthorized access, critical information is shielded from prying eyes. Additionally, a novel structure for controlling access that allows for the verifiable implementation of access restrictions in a cloud context is proposed in our study. By utilizing cryptographic methods like digitally signed documents and authorization tokens, the suggested approach guarantees that only those with permission may access certain data resources. Furthermore, by including strong audit trails and logging systems, administrators may monitor and confirm access attempts with great care, improving access management transparency and accountability.